Circulating Galectin-3 levels in women with polycystic ovary syndrome: A meta-analysis - Seyed Sobhan Bahreiny; Mohammad-Navid Bastani; Mojtaba Aghaei; Mohammad Reza Dabbagh; Amir Hossein Mahdizade (Taiwanese Journal of Obstetrics & Gynecology, 2024)
Polycystic ovary syndrome (PCOS) is a highly prevalent endocrine disorder characterized by multifactorial and intricate pathogenesis. The discovery of novel markers has been a significant step toward understanding the mechanisms of PCOS. Galectin-3 has emerged as a novel factor in metabolic disorders. This meta-analysis examines the association between circulating Galectin-3 and PCOS. A systematic review and meta-analysis were performed to identify relevant articles in the electronic databases PubMed, Web of Science, Scopus, Cochrane, EMBASE, and Google Scholar. The search covered the period from January 2000 to March 2023 and followed a predefined search strategy. Eight articles were included in the analysis with a total of 594 participants (322 patients with PCOS and 272 controls). Pooled standardized mean difference (SMD) and 95 % confidence interval [CI] were used to evaluate the association between Galectin-3 levels and PCOS. The results indicated a significant association between PCOS and galectin-3 levels (SMD = 0.58; 95 % CI: 0.15–1.01; p = 0.007). In addition, subgroup analysis showed a significant difference in serum Galectin-3 levels in women with PCOS and a higher homeostatic model assessment for insulin resistance ratio (SMD = 0.89; 95 % CI: 0.45–1.33; p < 0.001). The researchers also performed meta-regression and subgroup analyses to specify sources of heterogeneity. The results of our meta-analysis suggest an association between increased levels of galectin-3 and PCOS. Galectin-3 plays a significant role in the progression of PCOS and could be used as a novel diagnostic biomarker. Nevertheless, it is essential to perform further studies to confirm and support our conclusions.